Germany - VET in Europe - Country report 2014 - Hensen-Reifgens, Kristina Alice [Verfasser]; Hippach-Schneider, Ute [Verfasser] (Bundesinstitut für Berufsbildung, 2015)
"This report gives an overview of the VET system in Germany. Information is presented according to the following themes: 1. External factors influencing VET; 2. Providing VET in a lifelong learning perspective; 3. Shaping VET qualifications; 4. Promoting participation on vocational education and training." (Authors' abstract, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.5.2 Berufliche Weiterbildung; S 4.1 Finanzierungsquellen; I 2.1 Deutschland; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Bildungsfinanzierung; Bundesrepublik Deutschland